2014
DOI: 10.1080/09168451.2014.925778
|View full text |Cite
|
Sign up to set email alerts
|

Effect of seasonal and experimental temperature on de novo synthesis of fatty acids in C. crangon

Abstract: The intensity of in vivo lipogensis was measured and in this purpose, the radioactivity of incorporation of tritium into fatty acids (FAs) in tissues of C. crangon was determined. De novo synthesis of FAs was five times higher in hepatopancreas than in muscle in summer period but not much higher in autumn. The higher FAs synthesis was recorded at 25 °C, both for hepatopancreas and muscle, and the summer was higher than the autumn in the hepatopancreas and in the muscles of the opposite situation was observed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…On the other hand, the levels of n-6 PUFA were conserved while n-3 PUFA and LC-PUFA levels were magnified in both the muscle and hepatopacreas during the coldstress. At reduced temperatures, in their study with C. crangon, Mika et al (2014) reported similar response as also did also Perez-Velazquez et al (2003) with L. vannamei. Despite partial starvation coupled with the cold-stress, the significant accumulations of PUFA and LC-PUFA recorded in the tissues of P. semisulcatus might be due to the vital role of these fatty acids in membrane structures of shrimp (Farkas, 1979;Schlechtriem et al, 2006;Werbrouck et al, 2016a).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…On the other hand, the levels of n-6 PUFA were conserved while n-3 PUFA and LC-PUFA levels were magnified in both the muscle and hepatopacreas during the coldstress. At reduced temperatures, in their study with C. crangon, Mika et al (2014) reported similar response as also did also Perez-Velazquez et al (2003) with L. vannamei. Despite partial starvation coupled with the cold-stress, the significant accumulations of PUFA and LC-PUFA recorded in the tissues of P. semisulcatus might be due to the vital role of these fatty acids in membrane structures of shrimp (Farkas, 1979;Schlechtriem et al, 2006;Werbrouck et al, 2016a).…”
Section: Discussionmentioning
confidence: 56%
“…Chapelle (1978) acclimated the crab C. maenas to temperatures of 7, 14 and 27°C and observed the greatest differences in the relative content of 16:0, 16:1, 18:0, 18:1, 20:5 and 22:6 fatty acids in relation to temperature. It is suggested by many authors that acclimation temperature involves in the degree of unsaturation of cellular lipids in order to maintain fluidity of cell membranes essential for biological activities (Sinensky, 1974;Dey, Buda, Wiik, Halver, & Farkas, 1993;Perez-Velazquez et al, 2003;Schlechtriem et al, 2006;Mika, Skorkowski, & Stepnowski, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that marine crustaceans (e.g. Crangon crangon : Mika et al ., 2014) and freshwater crustaceans (e.g. Macrobrachium rosenbergii : Reigh & Stickney, 1989) are capable of enzymatically transforming scPUFA into lcPUFA.…”
Section: Discussionmentioning
confidence: 99%